A SMART SENSING MODULE AIMS AT REDUCTION OF MOTION ARTIFACT FOR WEARABLE TONOMETRY BLOOD PRESSURE DEVICE. (June 2022) - Liu, Weiting; Zhu, Tao; Xie, Fuyuan; Zhan, Binpeng; Xu, Man
Abstract : Objective: This work focuses on development a unique mini sensing module to alleviate muscle action induced rtefacts and in the meanwhile to enable the alignment free capability for radial BP measurement. Design and method: The coupling variations from motion rtefacts tremendously distorts the sensing signal thus leads the measuring results unreliable and limits the applications of wearable blood pressure monitoring in daily life. It is key to have capability of sensing and recognizing the muscle action induced stress at the measuring site and then have the opportunity to eliminate misleading coupling variation. The mini sensing module consists of two independent sensing channels, which are neighboring distributed in parallel (Fig. 1). The channels are arranged enough close with the spacing only 2 mm in order to guarantee them sensing the same induced stress. The two channels have identical dimension feature with10 mm length and 3 mm width. And a 3 mm × 3 mm hard block is integrated into the middle segment of one channel. The channels are filled with degassed silicon oil and a silicon die is embedded and serves as pressure sensor unit. TPU flexible film is used to seal the channels, which serves also as the mechanical stimulation interface. The smart module is fixed to wrist with channel direction transversal to the arterial path during radial BP measuring. The blocked channel isolates completely (partly at least) stimulating from the vascular and serves as skin stress sensing reference, and the other sensing channel gets combination of the skin stress together with fully stimulating of vascular BP. It is straightforward that the difference two signal can partly at least eliminate the stress induced error, which also is presented in Fig.2. Further rtefacts reduction can be achieved by exploiting specific adaptive filtering algorithm with the blocked signal as disturbance input and the other as source. Results: Experiments have proved the effectiveness of the scheme. Conclusions: By comparison with the BP signal under optimal condition, the sensing module can provide with accurate BP pulse waves in the presence of motion interference.